(untitled) (Discourse of Law and Administration, 2021)
Expropriation of real estate consists in the deprivation or limitation of ownership by way of a decision; perpetual usufruct or other right in rem in real estate. It will therefore consist in limiting the owner’s rights to own, use and dispose of the thing. The greatest interference with our property will therefore be to take away the above-mentioned rights. However, expropriation of real estate is allowed only when it is carried out for public purposes and for just compensation.